Determinants of Participation in The Utilization of Islamic Microfinance Products: Empirical Studies Using the Theory of Planned Behavior (TPB) Approach in Indonesia - Iqbal ‘Imari; Hartomi Maulana; Mohd. Zaidi Bin Md Zabri; Ahmad Suminto (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2023)
Introduction: It is hoped that the presence of Islamic microfinance in Muslim countries will not only pursue each other and increase productivity to increase their assets. However, Islamic microfinance is hoped to be able to provide benefits to the whole community, especially in eradicating poverty. The phenomenon, it becomes the basis for research to measure the determinants of participation in the utilization of Islamic microfinance products using the TPB approach in Indonesia Islamic microfinance. Purpose: This research has a purpose to measure the determinants of participation in the utilization of Islamic microfinance products. The model hypothesized that three factors, attitude, subjective norms and Perceived Behavior Control influence customers participation in the utilization of Islamic microfinance products. Methodology: This research uses a descriptive-quantitative-analytic method or approach with several stages, namely testing hypotheses, measuring data, interpretation and description of results and making conclusions. This research using primary data by questionnaires distributed to customers of Islamic financing products in Islamic microfinance. Data collection method using simple random sampling and the data analysis technique uses Structural Equation Modeling (SEM) with the Smart PLS-3 application. Findings: The research results show that attitude directly has a significant positive effect on intentions in participation behavior in utilizing Islamic microfinance products at Islamic microfinance institutions. Meanwhile, indirectly attitudes are formed and influenced by awareness, compability, complexity and relative advantadge variables. This finding also confirms that subjective norms originating from a person's group and the perceived pressure from a person's reference to carry out targeted behavior can influence the intentions in participation behavior in utilizing Islamic microfinance products at Islamic microfinance institutions. Other findings that perceived behavioral control results is increased, when individuals feel they have more resources and confidence to perform. Perceived behavior control as measured by individual perceptions about the extent to which behavior performance is easy or difficult and considers facilitators and barriers to doing so has a significant effect on the intention to utilizing Islamic microfinance products.